APPLICATION OF JEAN PIAGET'S COGNITIVE LEARNING THEORY IN EARLY CHILDHOOD EDUCATION - Lucia Sriastuti; Musa Masing (SOKO GURU: Jurnal Ilmu Pendidikan, 2022)
Learning is generally a mental or psychic activity carried out by a person so that it causes changes in behavior that are different between after learning and before learning. Learning according to cognitive theory is a business process that involves mental activities that occur in humans as a result of the process of active interaction with the environment to obtain a change in the form of knowledge, understanding, behavior, skills and attitude values ​​that are relativ and have scars. By understanding cognitive learning theory, teachers will be able to provide learning and facilitate children's learning in a more focused and appropriate manner in accordance with the child's developmental stage. In Jean Piaget's cognitive theory, early childhood enters the first two stages of development, namely the sensorimotor stage and the pre-operational stage. This paper uses the Systemic Literature Review method, which is a method of collecting literature related to the topic of the problem being studied, both from journals, books and other sources relevant to the research topic.